Bacterial and viral indicators of fecal contamination in drinking water. Issue 4 (1st April 2014) - Plummer, Jeanine D.; Long, Sharon C.; Charest, Abigail J.; Roop, Daniel O.
Abstract : Coliform indicators are used as an index of waterborne disease risk. Coliforms respond differently to environmental stressors and engineered treatment processes than viral pathogens and thus are imperfect indicators. Bacteriophages, which are similar in structure and morphology to human enteric viruses, may be more highly correlated with the presence of viral pathogens. In this research, coliforms, Escherichia coli, male‐specific coliphages, and somatic coliphages were quantified in feces and in wastewater and drinking water samples collected in multiple regions and seasons. Physical and chemical water quality were also measured. Bacterial indicators varied with animal type in feces and varied with treatment stage in wastewater and drinking water. Samples analyzed for coliphages had a high number of nondetects (49% in fecal samples and up to 79% in drinking water samples), but coliphages can be analyzed in addition to bacteria to provide complementary information on fecal contamination in water and public health risk. In some cases, turbidity and organic carbon may provide a rapid indication of pollution that could trigger targeted microbiological monitoring.